Optical and photocatalytic properties of bismuth vanadate doped bismuth silicate glasses - Apichart Limpichaipanit (2019)
© 2019 Elsevier GmbH The aim of this research is to investigate optical and photocatalytic properties of 0.25, 0.5 and 1.0 mol% BiVO 4 doped bismuth silicate glasses. The glasses composition is 60 mol% SiO 2 and 40 mol% Bi 2 O 3 . Optical spectra and the analysis of color by CIELab system revealed that the addition of BiVO 4 changed the color of the glasses from pale yellow to yellow-orange with the narrower band gap. Photocatalytic activity was observed in 0.5 and 1.0 mol% BiVO 4 -doped glass. The effect of BiVO 4 doping to bismuth silicate glass is also discussed.